2022
DOI: 10.1186/s40249-022-01043-2
|View full text |Cite
|
Sign up to set email alerts
|

The rapid and efficient strategy for SARS-CoV-2 Omicron transmission control: analysis of outbreaks at the city level

Abstract: Background Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) Omicron (B.1.1.529) variant is highly transmissible with potential immune escape. Hence, control measures are continuously being optimized to guard against large-scale coronavirus disease 2019 (COVID-19) outbreaks. This study aimed to explore the relationship between the intensity of control measures in response to different SARS-CoV-2 variants and the degree of outbreak control at city level. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…In this study, we described and compared the epidemiological characteristics of outbreaks, caused by the Delta variant in 2021 and Omicron subvariants in summer 2022 in mainland China. We observed that Omicron subvariants spread more widely than Delta subvariants to all provinces in China, resulting in substantially higher case numbers in each outbreak and prolonged outbreaks [ 17 ]. The Omicron outbreaks in summer 2022 could not be controlled as effectively as for Delta [ 18 ] even with more intensive control measures corresponding to more substantial reductions in population mobility and higher vaccine coverage.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we described and compared the epidemiological characteristics of outbreaks, caused by the Delta variant in 2021 and Omicron subvariants in summer 2022 in mainland China. We observed that Omicron subvariants spread more widely than Delta subvariants to all provinces in China, resulting in substantially higher case numbers in each outbreak and prolonged outbreaks [ 17 ]. The Omicron outbreaks in summer 2022 could not be controlled as effectively as for Delta [ 18 ] even with more intensive control measures corresponding to more substantial reductions in population mobility and higher vaccine coverage.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has also shown that as long as NPIs are strong enough, that is, the diagnostic rate and isolation rate are both high, then the government’s response time is much less sensitive to outbreaks. This indicates that strong control efforts have quite significant inhibitory effects on the spread of COVID-19 [ 55 ]. Under the same conditions, social activity control can be dynamically adjusted according to the daily number of reported cases to keep the outbreak at a low level.…”
Section: Discussionmentioning
confidence: 99%
“…It is challenging to strike a balance between epidemic prevention and control and economic and social development. Each country and city may have its own unique circumstances that require additional considerations and adaptations [ 1 ]. China has a population of 1.41 billion.…”
Section: Reopening Policymentioning
confidence: 99%